X-Linked Lissencephaly with ARX Mutations, Abnormal Genitalia, and Corpus Callosum Agenesis - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical and genetic findings of two X-linked lissencephaly with abnormal genitalia (XLAG) pedigrees with ARX mutations are reported from the University of Regensburg, Germany.